Exploring immunotherapeutic strategies for neurodegenerative diseases: a focus on Huntington’s disease and Prion diseases - Mukherjee Abhiyanta; Biswas Soumojit; Roy Ipsita (Acta Pharmacologica Sinica, 2025)
Immunotherapy has emerged as a promising therapeutic approach for the treatment of neurodegenerative disorders, which are characterized by the progressive loss of neurons and impaired cognitive functions. In this review, active and passive immunotherapeutic strategies that help address the underlying pathophysiology of Huntington’s disease (HD) and prion diseases by modulating the immune system are discussed. The current landscape of immunotherapeutic strategies, including monoclonal antibodies and vaccine-based approaches, to treat these diseases is highlighted, along with their potential benefits and mechanisms of action. Immunotherapy generally works by targeting disease-specific proteins, which serve as the pathological hallmarks of these diseases. Additionally, the review addresses the challenges and limitations associated with immunotherapy. For HD, immunotherapeutic approaches focus on neutralizing the toxic effects of mutant huntingtin and tau proteins, thereby reducing neurotoxicity. Immunotherapeutic approaches targeting flanking sequences, rather than the polyglutamine tract in the mutant huntingtin protein, have yielded promising outcomes for patients with HD. In prion diseases, therapies attempt to prevent or eliminate misfolded proteins that cause neurodegeneration. The major challenge in prion diseases is immune tolerance. Approaches to overcome the highly tolerogenic nature of the prion protein have been discussed. A common hurdle in delivering antibodies is the blood‒brain barrier, and strategies that can breach this barrier are being investigated. As protein aggregation and neurotoxicity are related, immunotherapeutic strategies being developed for other neurodegenerative diseases could be repurposed to target protein aggregation in HD and prion diseases. While significant advances in this field have been achieved, continued research and development are necessary to overcome the existing limitations, which will help in shaping the future of immunotherapy as a strategy for managing neurological disorders.